Feelings in the realm of moral (Educação e Pesquisa, 2003)
The purpose of this article is to analyze the organizing models constructed in the resolution of an interpersonal conflict in which a young girl gives up the fulfillment of a wish in favor of her companion. The experimental setup is organized in such a way that the results obtained allow detecting and analyzing in detail distinct forms of articulating the affective and moral facets involved in the resolution of a surrender in which gender connotations play an important role. Subjects were asked to resolve the same conflict from three different perspectives: Justice, Happiness and Help. While from certain theoretical approaches feelings are regarded as disturbing elements of moral reasoning, the organizing models approach showed that considering first the emotional aspects of a conflict can have positive repercussions to the analysis from a perspective of justice. Also, gender differences were detected unrelated either to the structural level or to the moral orientation. The way in which girls and boys gave substance to the conflict differed, and so did the dynamics they established between justice and happiness.